Representações de gênero na Aracaju ficcional de Amando Fontes : uma análise da obra Os Corumbas - Melo, Andréa Patrícia Santos (2014)
This work aimed to reflect about the interactions between History and Literature, discussing issues such as the truth in History and Literature, and the uses of literary work by historian. This research has chosen as the work corpus Corumbas (1933), the writer Amando Fontes, one of the main representatives of the literary movement known as Romance of 30, which brought brazilian literature a concern sharper in ally the art with social denunciation. Currently, in its 25th edition, this work constitutes an interesting source of research for analysis of various aspects of the history of Sergipe and, in particular, of Aracaju, raising debates still present. The daily work in the factories and the forms of leisure in the city of Aracaju in the early 20th century are some of the topics discussed by Amando Fontes, which were also the target of interest of researchers and critics. Our analysis started from a targeted perspective to a field still unexplored in the work, seeking to understand the aspects of gender relations. Initially, we conducted a bibliographic and documentary research work, observing the criticisms produced at the time of the publication of the novel, as well as the studies carried in the graduate, the example of dissertations that focused on the writer and his novels, realizing its insertion in the literary scene of the 30 and its contribution to the History of Brazilian Literature. Then we discussed issues concerning possible relationships between History and Literature, seeking to understand the fictional Aracaju portrayed by the author. At the end of our work, we investigated the construction of sexual roles established for men and women. Through the analysis of the main characters and their representations, we observe the values, worldviews, moral conceptions and taboos that permeated society from Aracaju and how these elements are included in the writing of novelist. We believe that this study reveals important issues about gender relations in the early 20th century, opening up new research possibilities for historians and literati.